(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The objective of the research is to study the effect of brand personality on customer loyalty by examining the effect of brand personality dimensions namely Sincerity, Excitement, Competence, Sophistication, Ruggedness on customer loyalty. A questionnaire was designed and distributed to a convenient sample of brand consumers of smart phones in Lattakia Governorate. The study results indicate that there is a positive effect of the brand personality the on customer loyalty, and sofistication has had the greatest effect on customer loyalty, whereas Competence has had the least effect on customer loyalty. هدف البحث إلى دراسة تأثير شخصية العلامة التجارية على ولاء العميل وذلك من خلال دراسة تأثير أبعاد شخصية العلامة التجارية وهي الصدق، الإثارة، الكفاءة، درجة التطور، الصلابة على ولاء العميل. حيث تم تصميم استبيان وتوزيعه على عينة ميسرة من مستهلكي الأجهزة المحمولة الذكية في محافظة اللاذقية. وتوصل البحث إلى أن هناك تأثير إيجابي لشخصية العلامة التجارية على ولاء العميل وكانت درجة التطور هي صاحبة التأثير الأكبر على ولاء العميل أما الكفاءة فكانت صاحبة التأثير الأقل على ولاء العميل.